Long-Term Clinical, Radiographic, and Cost Analysis of Corrective Spine Surgery for Adult Symptomatic Lumbar Deformity With a Mean of 7.5 years Follow-Up. Issue 5 (1st March 2023) - Yagi, Mitsuru; Shimizu, Toshiyuki; Suzuki, Satoshi; Takahashi, Yohei; Ozaki, Masahiro; Tsuji, Osahiko; Nagoshi, Narihito; Yato, Yoshiyuki; Matsumoto, Morio; Nakamura, Masaya; Watanabe, Kota; ,
Abstract : Study Design: Multicenter retrospective study. Objective: This study reports long-term clinical and radiographic outcomes in surgically treated patients with adult symptomatic lumbar deformity (ASLD). Summary of Background Data: The short-term results of corrective spinal surgery for ASLD are often favorable despite a relatively high complication profile. However, long-term outcomes have not been completely characterized. Methods: A total of 169 surgically treated consecutive ASLD patients (≥50 yr) who achieved minimum 5 year follow-up were included (average 7.5 yr observation window, average age 67±8 yr, 96% female). The subjects were stratified by current age (50s, 60s, and 70s) and compared. Kaplan-Meier analysis was used to estimate the cumulative incidence of unplanned reoperation stratified by age group. Initial and overall direct costs of surgery were also analyzed. Results: The SRS-22 at final follow-up was similar among the three groups (50s, 60s, and 70s; 4.0±0.5 vs. 3.8±0.7 vs. 3.8±0.7, respectively). The overall major complication rate was 56%, and 12% experienced late complications. The cumulative reoperation rate was 23%, and 4% required late reoperation. Patients in their 70s had a significantly higher reoperation rate (33%) and overall complication rate (65%). However, the late complication rate was not significantly different between the three groups (9% vs. 12% vs. 13%). Sagittal alignment was improved at two years and maintained to the final follow-up, whereas reciprocal thoracic kyphosis developed in all age groups. The direct cost of initial surgery was $45K±9K and increased by 13% ($53K±13K) at final follow-up. Conclusions: Long-term surgical outcomes for ASLDs were favorable, with a relatively low rate of late-stage complications and reoperations, as well as reasonable direct costs. Despite the higher reoperation and complication rate, ASLD patients of more advanced age achieved similar improvement to those in the younger age groups.